2020
DOI: 10.2147/ndt.s185757
|View full text |Cite
|
Sign up to set email alerts
|

<p>Selective Serotonin Reuptake Inhibitor-Induced Sexual Dysfunction: Current Management Perspectives</p>

Abstract: Any type of sexual dysfunction is an important problem in half of the patients with depressive disorder. On the other hand, one to a quarter of people without any depressive disorder experience sexual dysfunction. Antidepressant agents can lead to all types of sexual side effects including arousal, libido, orgasm and ejaculation problems. Selective serotonin reuptake inhibitors (SSRIs) are a widely used class of drugs which are prescribed for the treatment of a variety of disorders, including major depressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 67 publications
0
36
0
7
Order By: Relevance
“…Mood disorders, such as depression, are mainly caused by chronic stress or stressful events, with a high lifetime prevalence of reaching 20% ( Patten, 2003 ). Sexual dysfunction, characterized by decreased sexual motivation and impaired sexual performance, is a major comorbidity in men with depression ( Clayton et al, 2013 ) and current therapies are only partially effective, with a slow onset of efficacy, and may even lead to more severe sexual dysfunction ( Atmaca, 2020 ). In the present study, we found that treatment with SSD can not only generate a stable antidepressant effect but also significantly alleviate sexual dysfunctions in CMS mice.…”
Section: Discussionmentioning
confidence: 99%
“…Mood disorders, such as depression, are mainly caused by chronic stress or stressful events, with a high lifetime prevalence of reaching 20% ( Patten, 2003 ). Sexual dysfunction, characterized by decreased sexual motivation and impaired sexual performance, is a major comorbidity in men with depression ( Clayton et al, 2013 ) and current therapies are only partially effective, with a slow onset of efficacy, and may even lead to more severe sexual dysfunction ( Atmaca, 2020 ). In the present study, we found that treatment with SSD can not only generate a stable antidepressant effect but also significantly alleviate sexual dysfunctions in CMS mice.…”
Section: Discussionmentioning
confidence: 99%
“…As might be expected, male partners suffer too from the consequences of the partner’s discomfort, showing increased rates of psychological distress, with a higher prevalence of sexual difficulties (e.g., erectile dysfunction), and less sexual satisfaction [ 205 , 206 , 207 , 208 ]. At the same time, it should never be overlooked that psychopharmacological therapy as well as hormone therapy can in their turn affect the sexual activity of women who have endometriosis [ 209 , 210 , 211 ]. It follows that gynecological and pain management treatment cannot be separated from a scrupulous psychiatric assessment in terms of clinical efficacy and prognosis.…”
Section: Final Remarksmentioning
confidence: 99%
“…(22) Follow-up with a psychiatrist together with a gynecologist is highly recommended. (23) The management of sexual dysfunction induced by serotonin reuptake inhibitors may include discussing the possibility of adding/changing medication by the psychiatrist (Chart 2). ity may lead to contraceptive discontinuation.…”
Section: What Are the Most Common Biologic Factors Related To Hsdd In Women In Gynecologic Routine Care?mentioning
confidence: 99%